Implementasi Konsep “Blue Economy” Dalam Meningkatkan Pendapatan Nelayan Di Kota Medan Perspektif Ekonomi Syariah (Studi Kasus:Kecamatan Medan Labuhan) - Alfaqih Tariq Aziziy Hasibuan; Rahmi Syahriza; Muhammad Syahbudi (CV. ITTC INDONESIA, 2023)
Blue Economy is ecosystem-based management to take full advantage of well-managed marine resources to carry out cross-sectoral coordination with public-private partnerships and investments that will provide benefits for the country's economic income by continuing to develop the future potential of marine-based economic resources. The blue economy can create great opportunities to overcome problems in coastal areas by overcoming the challenges they pose. The aim of this research is to determine the implementation of the